Effect of dietary Terminalia sericea aqueous leaf extracts on high-fructose diet fed growing Wistar rats - Lembede, Busisani Wiseman (My University, 2014)
Sedentary lifestyles and poor dietary choices are the major cause of the global increase in the prevalence of obesity and metabolic dysfunction in children. The high cost and limited access to conventional drugs by poor communities make them depend on ethnomedicines. Terminalia sericea (T. sericea) contains phytochemicals that give its extracts hypolipidaemic and hypoglycaemic properties hence its use in ethnomedicine to treat diabetes mellitus. Using weanling Wistar rat pups fed a high fructose diet to model growing children exposed to high-sugar diets, this study sought to evaluate the effects of aqueous T. sericea leaf extracts on their growth performance, glucose homeostasis, visceral morphometry and their general health profile. Forty 21-day old male Wistar pups were randomly allocated to five treatment regimens. Each group had ad libitum access to a commercially supplied rat chow. Group 1 pups were given plain drinking water and plain gelatine cubes, group 2: 12% fructose solution and plain gelatine cubes, group 3: 12% fructose solution and gelatine cubes containing fenofibrate at a dosage of 100 mg.kg-1 per day, group 4: 12% fructose solution and gelatine cubes with a low dose (100 mg.kg-1 per day) of the T. sericea extract and group 5: 12% fructose solution and gelatine cubes with a high dose (400 mg.kg-1 per day) of the T. sericea extract. The pups were maintained on the regimens for 12 weeks after which they under went an oral glucose tolerance test. Fasting blood metabolite content was then determined after which the rats were killed and tissues collected for visceral morphometrical, linear growth and surrogate markers’ of health determinations. T. sericea extracts had no negative effect on growth performance (body mass and indexes of long bone growth) but rats given fenofibrate had lighter empty carcasses and shorter tibiae. vi The administration of T. sericea extracts neither improved glucose homeostasis nor caused derangement of glucose handling by rats given a high fructose diet following an oral glucose challenge. However, the administration of fenofibrate to rats given a high fructose diet resulted in decreased glucose handling following an oral glucose challenge. With the exception of the administration of fenofibrate which resulted in a significantly high (P < 0.05) fasting blood glucose concentration, treatment regimens had no effect on fasting blood glucose, triglyceride and cholesterol concentrations. Rats given fructose with either plain gelatine cubes or low T. sericea dose had significantly higher (P < 0.05) liver lipid content compared with the control treatment. Administration of T. sericea extracts to rats given a high fructose diet had no effect on the GIT, other abdominal viscera and markers of general health. The administration of fenofibrate to rats given a high fructose diet caused increased relative mass of GIT organs (stomach, small intestine and caecum), increased absolute mass of other viscera (liver and kidney); increased serum phosphorus and alkaline phosphatase concentration. Results from the study revealed that administration of a high dose of aqueous T. sericea leaf extracts has potent phytochemicals properties that has helped to prevent high fructose diet-induced deposition of fat in the in the liver (non-alcoholic fatty liver disease), without compromising growth, visceral morphometry and general health of growing Wistar rats.
A dissertation submitted to the Faculty of Health Sciences, University of Witwatersrand, School of Physiology in fulfilment of the requirements for the degree of Master of Science in Medicine. Johannesburg, 2014
Keywords: Plants, Medicinal--therapeutic use; Rats; Terminalia; Diet